2011
DOI: 10.1002/j.1556-6676.2011.tb02836.x
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices: A Critical Yet Inclusive Vision for the Counseling Profession

Abstract: Substantial controversy has surrounded the concept of best practices (BPs) in counseling; in particular, the consequences of deriving practice guidelines from empirically supported treatments (ESTs). Criticisms of EST methodology, assumptions, and findings are summarized, and implications for core counseling values, including multiculturalism, are discussed. The authors further elaborate an inclusive view of BP that can facilitate the use of research to inform and enhance counseling services while rectifying p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Practice guidelines, influenced by federal agencies and professional organizations, that standardize treatments into a one‐size‐fits‐all treatment approach were developed with the belief that they would alleviate anxiety and establish accountability (Singh & Oswald, ; Spring, ). These guidelines culminated in the development of the EBP movement and the creation of the concept of best practices (Marquis et al, ), which seek to use emerging evidence to “invalidate previously accepted diagnostic treatments and replace them with new ones that are more powerful, more accurate, more efficacious, and safer” (Thyer, , p. 168).…”
Section: The Shift Toward the Objectifiablementioning
confidence: 99%
See 2 more Smart Citations
“…Practice guidelines, influenced by federal agencies and professional organizations, that standardize treatments into a one‐size‐fits‐all treatment approach were developed with the belief that they would alleviate anxiety and establish accountability (Singh & Oswald, ; Spring, ). These guidelines culminated in the development of the EBP movement and the creation of the concept of best practices (Marquis et al, ), which seek to use emerging evidence to “invalidate previously accepted diagnostic treatments and replace them with new ones that are more powerful, more accurate, more efficacious, and safer” (Thyer, , p. 168).…”
Section: The Shift Toward the Objectifiablementioning
confidence: 99%
“…Both scholars and practitioners have critiqued the reductionistic paradigm, methodological limitations, and inability of EBPs to respond to the complex human experiences counselors are presented with in practice (Hansen, ; Lilienfeld, ; Marquis et al, ; Wampold & Bhati, ). Despite consistent complaints that EBPs threaten to marginalize more “nuanced, complex, and individualized” (Marquis et al, , p. 397) treatments and narrowly define best practices, the use of EBPs has become a dominant narrative affecting all facets of mental health culture—a narrative in which scientific evidence “must be accorded priority” (Lilienfeld, Ritschel, Lynn, Cautin, & Latzman, , p. 886) above clinical expertise and the preferences and values of clients. This belief has led to scientifically minded approaches (e.g., cognitive, behavioral) to become increasingly associated with EBPs and more subjective approaches on the outside looking in (Marquies & Douthit, ).…”
Section: The Shift Toward the Objectifiablementioning
confidence: 99%
See 1 more Smart Citation
“…When Chambless and Ollendick (2001) published their listing of ESTs, they used randomized clinical trials (RCTs) to demonstrate the highest level of evidence. Typical characteristics of RCTs are comparisons between a control and treatment group, randomization, the use of treatment manuals, the use of reliable assessments with sound psychometric properties, and the exclusion of clients who present more than one type of psychopathology (Marquis, Douthit, & Elliot, 2011). Chambless and Ollendick suggested that RCTs have a greater degree of validity and are less likely to have possible confounds and biases.…”
Section: Components Of Ebpmentioning
confidence: 99%
“…Many third‐party payers, including both private insurance and providers of public benefits, are pushing for short‐term, manualized, evidence‐based treatments for serious mental and emotional disorders (Marquis, Douthit, & Elliott, ). In turn, this push has a strong influence over counseling practices, because the entity that holds the money holds the power.…”
mentioning
confidence: 99%